Current Vision of Multilateralism: Towards a Renewed Post-Pandemic International Community - Maúrtua de Romaña, Oscar (2025)
The new policies that have emerged over the years and have been shaped, certainly, from the framework of the Second World War and the creation of two antagonistic ideologies, have marked the international agenda and established a point of no return in alliances. and cooperation between states. Thus, the States have been forming blocks of cooperation, assistance and integration from the common points that the nations have been finding, guided in turn, by clearly geopolitical issues. Thus, multilateralism appears, on the international horizon, as that manifestation of the States that seek to improve the situation that concerns them, through agreements between them and the creation of organizations that, within the framework of the functions provided by their Founding letters, can host meetings, treaties and conferences in the search for consensus and the preservation of international security. The truth is that the pandemic has allowed the paradigms to change, that multilateralismfaces a series of challenges that are gradually being updated and suggests a change in the horizon of alliances between States and, above all, allow new actors appear on the international spectrum to contribute to the international obligations that international society requires to survive and return to normalcy with, of course, a new community system.